Unleashing the Power of Data with Trusted AI. - Wendy Turner-Williams; PACKT (GB: Packt, 2024)
Discover the transformative potential of AI for data-driven decision-making and fast-track your organization's growth journey with trusted AI implementation Key Features Gain comprehensive insights and analyses to make quick and accurate decisions Learn to integrate trusted AI into your organizational workflows and decision-making processes Explore real-world case studies that showcase the transformative impact of AI in diverse industries Purchase of the print or Kindle book includes a free PDF eBook Book Description Written by a distinguished leader and innovator who has been instrumental in spearheading digital, cloud, and AI transformations across global brands, Unleashing the Power of Data with Trusted AI is an indispensable resource that will make you AI-ready. This comprehensive guide is designed to meet the urgent need for clarity and to give you actionable insights into today's rapidly evolving landscape of AI and its fundamental driver - data. You'll delve into the exciting world of AI and its integration with data, uncover its significance, ethical considerations, and strategic applications with real-life success stories from industry giants like Starbucks, Netflix, and Siemens. You'll also witness first-hand how the integration of data and AI has reshaped markets and elevated customer experiences, and discover the future of generative AI based on several surveys and case studies. You'll gain an understanding of how AI has evolved across industries, empowering decision-making and fostering innovation. Tailored for board members, executives, innovators, and tech enthusiasts, this immersive guide will reshape your understanding of data and AI synergy. By the end of this guide, you'll be able to lead your teams, customers, partners, and organizations confidently and responsibly in the era of AI. What you will learn Navigate ethical considerations and comply with data regulations effectively Elevate data quality and enhance data literacy within your organization Craft effective AI strategies for data analytics processes Explore real-world case studies showcasing the tangible benefits of trusted AI Optimize decision-making processes by harnessing AI-driven insights Who this book is for This report is for executives and board members of mid to large enterprises, such as CDAIOs, CTOs, CIOs, CISOs, CPOs, and CEOs, as well as AI, data, ethics, privacy, and security professionals. With this book, you'll confidently develop your data and AI implementation strategy and navigate the complex landscape of emerging technologies with clarity.
Data in extended ASCII character set.
Mode of access: Internet.